MODEL PERANCANGAN SISTEM INFORMASI DALAM MENDUKUNG KETAHANAN PANGAN - Rosadi, Dadi; Sidharta, Iwan (Majalah Bisnis & IPTEK, 2016)
Rapid technological advances that increasingly requires the application of technological advances stretcher. One model of information technology development by building a system of information in this case the expert system that can diagnose diseases of rice plants. By using an expert system is expected to assist in providing a facility that supports to provide information and diagnose symptoms rice plants which arise along with the cause, especially that caused by pathogens to farmers in real time, and can be an alternative to meet the shortfall of field educator staff field which provides information on the prevention and control of pests and diseases of rice plants to farmers. Keywords: information systems; expert system; rice plant diseases.